Palladium, rhodium and platinum complexes of ortho-xylyl-linked bis-N-heterocyclic carbenes: Synthesis, structure and catalytic activity - Baker, M.; Brown, David; Simpson, P.; Skelton, B.; White, A.; Williams, C. (Elsevier, 2006)
New Pd(II), Pt(II) and Rh(I) N-heterocyclic carbene (NHC) complexes containing two NHC units linked by an ortho-xylyl group are described and structurally and spectroscopically characterised. The Pt(II) complexes represent the first examples of Pt-bis(NHC) complexes where the NHC units are linked by an ortho-xylyl group. Functionalisation of the bis(NHC) ligands with heptyl groups has been used as a means of enhancing the solubility of the complexes, in order to facilitate spectroscopic characterisation and catalytic studies. The catalytic activity of the palladium(II) complexes in Heck and Suzuki cross-coupling reactions has been examined to investigate any effects of the diverse structural changes, though these appear to be insignificant.